Adaptation of the group A Streptococcus adhesin Scl1 to bind fibronectin type III repeats within wound‐associated extracellular matrix: implications for cancer therapy. Issue 3 (12th June 2019) - McNitt, Dudley H.; Choi, Soo Jeon; Allen, Jessica L.; Hames, River A.; Weed, Scott A.; Van De Water, Livingston; Berisio, Rita; Lukomski, Slawomir
Summary: The human‐adapted pathogen group A Streptococcus (GAS) utilizes wounds as portals of entry into host tissue, wherein surface adhesins interact with the extracellular matrix, enabling bacterial colonization. The streptococcal collagen‐like protein 1 (Scl1) is a major adhesin of GAS that selectively binds to two fibronectin type III (FnIII) repeats within cellular fibronectin, specifically the alternatively spliced extra domains A and B, and the FnIII repeats within tenascin‐C. Binding to FnIII repeats was mediated through conserved structural determinants present within the Scl1 globular domain and facilitated GAS adherence and biofilm formation. Isoforms of cellular fibronectin that contain extra domains A and B, as well as tenascin‐C, are present for several days in the wound extracellular matrix. Scl1‐FnIII binding is therefore an example of GAS adaptation to the host's wound environment. Similarly, cellular fibronectin isoforms and tenascin‐C are present in the tumor microenvironment. Consistent with this, FnIII repeats mediate GAS attachment to and enhancement of biofilm formation on matrices deposited by cancer‐associated fibroblasts and osteosarcoma cells. These data collectively support the premise for utilization of the Scl1‐FnIII interaction as a novel method of anti‐neoplastic targeting in the tumor microenvironment. Abstract : Scl1 adhesin of GAS selectively binds to wound‐associated ECM proteins, extra domain A (EDA) and B (EDB) of cellular fibronectin and to tenascin‐C (TnC). The globular V domain of Scl1 mediates binding to ECM targets via conserved mechanism. Scl1‐ECM interactions facilitate GAS attachment and biofilm formation in the wound and promote host colonization.